Simulation of Wave-Flow-Cavitation Interaction Using a Compressible Homogenous Flow Method (Communications in Computational Physics, 2014)
A numerical method based on a homogeneous single-phase flow model ispresented to simulate the interaction between pressure wave and flow cavitation. Toaccount for compressibility effects of liquid water, cavitating flow is assumed to becompressible and governed by time-dependent Euler equations with proper equationof state (EOS). The isentropic one-fluid formulation is employed to model the cavitation inception and evolution, while pure liquid phase is modeled by Tait equationof state. Because of large stiffness of Tait EOS and great variation of sound speed inflow field, some of conventional compressible gasdynamics solvers are unstable andeven not applicable when extended to calculation of flow cavitation. To overcomethe difficulties, a Godunov-type, cell-centered finite volume method is generalized tonumerically integrate the governing equations on triangular mesh. The boundary istreated specially to ensure stability of the approach. The method proves to be stable,robust, accurate, time-efficient and oscillation-free.Novel numerical experiments are designed to investigate unsteady dynamics ofthe cavitating flow impacted by pressure wave, which is of great interest in engineering applications but has not been studied systematically so far. Numerical simulationindicates that cavity over cylinder can be induced to collapse if the object is accelerated suddenly and extremely high pressure pulse results almost instantaneously. This,however, may be avoided by changing the traveling speed smoothly. The accompanying huge pressure increase may damage underwater devices. However, cavity formedat relatively high upstream speed may be less distorted or affected by shock wave andcan recover fully from the initial deformation. It is observed that the cavitating flowstarting from a higher freestream velocity is more stable and more resilient with respect to perturbation than the flow with lower background speed. These findings mayshed some light on how to control cavitation development to avoid possible damageto operating devices.